2016
DOI: 10.4270/ruc.2016430
|View full text |Cite
|
Sign up to set email alerts
|

Non-Audit Services and Auditor Independence in an Environment of Low Investor Protection

Abstract: This paper aims to evaluate whether the provision of non-audit services (NASs) affects external auditor independence in an environment characterised by low legal protection of minority investors and a high concentration of ownership and control. Audit reports and costs of services are analysed over 3 years for 154 Brazilian companies. The binary variable proxy for independence indicates a qualified auditor's report and, as an alternative specification, the issuing of a going concern opinion. Logit models were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…This result indicates that respondents marginally support the above idea. The above result is consistent with most previous studies (Bloomfield & Shackman, 2008;Carmona et al, 2015;Sobrinho & Bortolon, 2016;Zhang et al, 2016). For instance, it is in line with what was reported in Norway by Zhang et al (2016), who concluded that providing of NAS does not suggest loss of independence; in Brazil by Sobrinho and Bortolon (2016) who concluded that the provision of NAS does not affect auditor independence.…”
Section: The Overall Samplesupporting
confidence: 92%
See 1 more Smart Citation
“…This result indicates that respondents marginally support the above idea. The above result is consistent with most previous studies (Bloomfield & Shackman, 2008;Carmona et al, 2015;Sobrinho & Bortolon, 2016;Zhang et al, 2016). For instance, it is in line with what was reported in Norway by Zhang et al (2016), who concluded that providing of NAS does not suggest loss of independence; in Brazil by Sobrinho and Bortolon (2016) who concluded that the provision of NAS does not affect auditor independence.…”
Section: The Overall Samplesupporting
confidence: 92%
“…Another study conducted by Sobrinho and Bortolon (2016) upon 154 Brazilian companies to evaluate whether the provision of NAS affects auditor independence. The results indicate that the provision of NAS does not affect auditor independence.…”
Section: The Provision Of Nas Has No Impact On Auditor Independencementioning
confidence: 99%
“…Dellai and Omri (2016) argue that avoiding non-audit activity serves as a shield, protecting an auditor from the danger of engaging in self-review, which might compromise the auditor's impartiality. In a similar vein, Sobrinho and Bortolon (2016) provide an alternative viewpoint based on their examination of 154 Brazilian companies. They assert that non-audit duties do not cloud the picture of auditor independence in any way.…”
Section: Empirical Literature Reviewmentioning
confidence: 99%